2018
DOI: 10.1001/jamanetworkopen.2018.6125
|View full text |Cite
|
Sign up to set email alerts
|

Association of Second-line Antidiabetic Medications With Cardiovascular Events Among Insured Adults With Type 2 Diabetes

Abstract: IMPORTANCE Understanding cardiovascular outcomes of initiating second-line antidiabetic medications (ADMs) may help inform treatment decisions after metformin alone is not sufficient or not tolerated. To date, no studies have compared the cardiovascular effects of all major second-line ADMs during this early decision point in the pharmacologic management of type 2 diabetes. OBJECTIVE To examine the association of second-line ADM classes with major adverse cardiovascular events. DESIGN, SETTING, AND PARTICIPANT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(126 citation statements)
references
References 75 publications
6
118
1
1
Order By: Relevance
“…While controversial, some studies suggest patients who take insulin may have a dose-dependent increased risk of cardiovascular events. [36][37][38][39] The possible increased cardiovascular morbidity may be related to weight gain and hypoglycemic events, which can accompany the use of sulfonylurea drugs and insulin particularly at higher doses. Highlighting the potential beneficial impact of the LCHF diet, in which sulfonylureas were routinely discontinued and insulin doses were initially reduced, and many of our patients in the LCHF group were able to further reduce or eliminate insulin.…”
Section: Discussionmentioning
confidence: 99%
“…While controversial, some studies suggest patients who take insulin may have a dose-dependent increased risk of cardiovascular events. [36][37][38][39] The possible increased cardiovascular morbidity may be related to weight gain and hypoglycemic events, which can accompany the use of sulfonylurea drugs and insulin particularly at higher doses. Highlighting the potential beneficial impact of the LCHF diet, in which sulfonylureas were routinely discontinued and insulin doses were initially reduced, and many of our patients in the LCHF group were able to further reduce or eliminate insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin, a traditional second‐line treatment for type 2 diabetes, leads to sodium and water retention, weight gain and hypoglycaemia, with resultant sympathetic nervous system activation . Theoretically, insulin may be detrimental to patients with concomitant HF, but this has yet to be tested in a randomized clinical trial in patients with established HF.…”
Section: Introductionmentioning
confidence: 99%
“…7 -10 Insulin, a traditional second-line treatment for type 2 diabetes, leads to sodium and water retention, weight gain and hypoglycaemia, with resultant sympathetic nervous system activation. 11,12 Theoretically, insulin may be detrimental to patients with concomitant HF, but this has yet to be tested in a randomized clinical trial in patients with established HF. In a post-hoc analysis of the Candesartan in Heart failure: Assessment of Reduction in Mortality and morbidity (CHARM) trial, insulin therapy was associated with higher risks of mortality and HF hospitalization in patients with HF and reduced ejection fraction (HFrEF) and similar findings have been reported from other HFrEF clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study that looked at CV risk associated with adding a second medication to type 2 patients treated with metformin, O'Brien reported that the newer medications conferred a significantly lower risk for incidence of a first major CV event compared with sulfonylurea or glargine treatment. 17 Moreover, in the EMPA-REG study, investigators reported significant reductions in CV events in T2D patients treated with empagliflozin (SGLT-2 inhibitor). 18 Other SGLT-1/SGLT-1&2 studies have also shown reductions in risk for renal disease.…”
Section: Lack Of Safety Studies For CV Riskmentioning
confidence: 99%